Anthropogenic Effects on Coastal Sediment Fluxes in a Nontidal Gulf System - Ostrowski, Rafał; Pruszak, Zbigniew; Babakov, Aleksander; Chubarenko, Boris (Journal of waterway, port, coastal, and ocean engineering, 2012)
AbstractThis paper presents the results of studies of the physical processes observed in the coastal zone of the eastern part of the Gulf of Gdańsk, from the Vistula river mouth (Poland) to Cape Taran (Russia, Kaliningrad Oblast), because it is under severe environmental and anthropogenic pressure. We present investigations of wind climate, wind-driven currents, deep-water waves, nearshore sediment fluxes, engineering activities, and shoreline changes/response at eight study sites selected along the coast of the study area. Four of the sites are located on the Polish side and four on the Russian side of the state border. An assessment of the anthropogenic impact on coastal litho- and morphodynamics (local sediment fluxes and shoreline response) as a function of different local hydrodynamic climates is performed. Key coastal locations in the Gulf (the Vistula river mouth, the Baltijsk Strait with the harbor of Baltijsk, and the mining plants near Jantarnyj), where natural sediment morphological processes have been affected by human activities, are particularly analyzed. Even in the same system (Gulf of Gdańsk), sites located close to each other and subject to similar anthropogenic activities can display quite different evolutionary patterns. In some cases, anthropogenic effects may be secondary to natural background conditions.